Analysis of effectiveness of internal control systems in managing education capitation grants in local government authorities in Tanzania - Temu, Edward (Mzumbe University, 2024)
The dissertation submitted in partial fulfillment of the requirements for awards of Degree of Masters of Science in Accounting and Finance (MSc. A and F) of the Mzumbe University